The Impact of Situational, Demographic and Socio-Economic Factors on Impulse Buying in the Republic of Macedonia - Ciunova shuleska, Anita (My University, 2012)
This study explores the role of situational, demographic, and socioeconomic variables in stimulating impulse purchase behavior in the Republic of Macedonia. Factor analysis reveals five categories of situational impulse buying factors: social and personal, in-store atmosphere, sales related, sales promotion, and time and money. Cluster analysis produced two segments: noticeably rational and noticeably impulsive. The results show significant differences between the two segments on all five factors of impulse buying. Furthermore, the results show that segments differ in terms of age, working status, household income, and frequency of buying.
Keywords: demographic factors, impulse buying, situational factors, socioeconomic factors